Adsorption filter
The adsorption filter with specific particle size and fixation ratios of adsorbent A and B addresses high pressure loss and variability issues, achieving high contaminant removal rates with reduced pressure loss.
Patent Information
- Application Number
- JP2023107690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing adsorption filters face issues with high pressure loss and performance variability due to the collapse of aggregates and filling of voids, particularly when using small particle diameters that increase pressure loss.
The adsorption filter design includes adsorbent A with an average particle length of 200 μm to 1000 μm and adsorbent B with an average particle length of 0.1 μm to 100 μm, with adsorbent B being fixed to the surface of adsorbent A in a ratio of 65% or more, creating a structure that maintains voids and reduces pressure loss.
This design enhances contaminant removal rates while minimizing pressure loss, improving the overall performance of the adsorption filter by increasing the surface area for adsorption and preventing clogging.
Smart Images

Figure 2025006715000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adsorptive filter for removing contaminants. [Background technology]
[0002] In recent years, as one of the measures to deal with environmental problems, interest in measures against odor pollution has been growing. For example, odor pollution is pollution caused by exhaust gas. Among exhaust gases, volatile organic compounds such as toluene and acetaldehyde are considered to be causative substances of sick house syndrome, and the removal and deodorization of these odorous substances is a major issue. It is known that these exhaust gases can be removed by filters attached to air purification devices such as air purifiers and air conditioners. It is preferable that this filter has low pressure loss, i.e., high breathability.
[0003] There is a high demand for a filter that has high pollutant removal performance and low pressure loss as a filter for removing the above-mentioned pollutants. In response to this demand, for example, in Patent Document 1, activated carbon particles of the same particle diameter are bonded and aggregated with a thermoplastic resin to form irregular aggregates, thereby creating voids between the aggregates, thereby realizing low pressure loss. In addition, in Patent Document 2, particles with an average particle diameter of 1 μm or less are supported on a nonwoven fabric, thereby achieving high volatile organic compound removal performance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3612329 [Patent Document 2] JP 2015-157250 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the filter of Patent Document 1 has problems such as the aggregates collapsing due to the external force applied when forming the adsorbent into a sheet, filling the voids and increasing the pressure loss, and the irregular structure of the formed aggregates results in a large variation in performance. Also, the filter of Patent Document 2 has problems such as the particle diameter of the particles used being small, and the adsorbent particles filling the voids between the nonwoven fibers, increasing the pressure loss.
[0006] In view of the above circumstances, an object of the present invention is to provide an adsorption filter that has high performance for removing pollutants such as volatile organic compounds and also has low pressure loss. [Means for solving the problem]
[0007] The adsorption filter according to an embodiment of the present invention that can solve the above problems is as follows. [1] An adsorption filter comprising: an adsorbent A having an average particle length of 200 μm to 1000 μm; an adsorbent B having an average particle length of 0.1 μm to 100 μm; and a substrate, wherein the adsorbent A and the adsorbent B are supported on the substrate, 500 or more particles of the adsorbent B are fixed to each particle of the adsorbent A, and when the total number of the adsorbents B is taken as 100%, 65% or more of the adsorbents B are fixed to the surface of the adsorbent A.
[0008] The above-mentioned adsorption filter contains adsorbent B having a small average particle major axis of 0.1 μm to 100 μm, so that the surface area for adsorbing contaminants can be increased, and the removal rate of contaminants can be increased. In addition, since 500 or more particles of adsorbent B having a small average particle major axis are fixed to the surface of adsorbent A having a large average particle major axis of 200 μm to 1000 μm, it becomes easy to create gaps between the adsorbent particles. In addition, since 65% or more of the total number of adsorbents B (100%) are fixed to the surface of adsorbent A, there is little adsorbent B that is free from the surface of adsorbent A, and it is possible to prevent adsorbent B from filling the gaps in the base material and causing clogging. This makes it possible to obtain an adsorption filter with low pressure loss.
[0009] The adsorption filter according to the embodiment of the present invention is preferably any one of the following items [2] to [8]. [2] Average particle length R of the adsorbent A A and the average particle length R of the adsorbent B B Ratio of R B / R A The adsorption filter according to [1], wherein the ratio of the surface roughness to the surface roughness is 1 / 5000 to 1 / 5. [3] Average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B , and the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) of the adsorbent A and the adsorbent B is P=R A 3 / [{(R A +2R B ) 3 -R A 3}×X], where X is 0.1 or more and 10 or less. [4] The adsorption filter according to any one of [1] to [3], wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite. [5] The adsorption filter according to any one of [1] to [4], wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite. [6] The adsorption filter according to any one of [1] to [5], wherein the adsorbent B is fixed to the surface of the adsorbent A via a binder. [7] The adsorption filter according to [6], wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof. [8] The adsorption filter according to any one of [1] to [7], wherein the substrate is a nonwoven fabric. Effect of the Invention
[0010] The above-mentioned adsorption filter can increase the removal rate of pollutants including volatile organic compounds and reduce pressure loss, thereby improving the pollutant removal performance. [Brief description of the drawings]
[0011] [Figure 1] 1 is a scanning electron microscope photograph of the adsorbent obtained in Example 2. [Diagram 2] 1 is a scanning electron microscope photograph of the adsorption filter obtained in Example 2 after the substrate was peeled off. [Diagram 3] 1 is a scanning electron microscope photograph of the adsorption filter obtained in Comparative Example 4 after the substrate was peeled off. [Figure 4] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss of the adsorption filters of Examples 1 to 16 and Comparative Examples 1 to 6. [Diagram 5] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss of the adsorption filters of Example 17 and Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the present invention will be described based on the embodiments. However, the present invention is not limited to the following embodiments, and can be modified as appropriate within the scope of the above and below described spirit, and all of these are included in the technical scope of the present invention.
[0013] An adsorption filter according to an embodiment of the present invention comprises adsorbent A having an average particle length of 200 μm to 1000 μm, adsorbent B having an average particle length of 0.1 μm to 100 μm, and a substrate, with adsorbent A and adsorbent B supported on the substrate, adsorbent B adhered to the surface of adsorbent A, and 500 or more particles of adsorbent B adhered to each particle of adsorbent A.
[0014] Adsorption occurs at the interface between the gas phase, liquid phase, or solid phase and the adsorbent, so that the adsorbed substance can be adsorbed to the adsorbent with high efficiency by increasing the contact probability at the interface between the adsorbent and the adsorbed substance. The adsorption filter according to the embodiment of the present invention contains the adsorbent B, which has a small average particle major axis of 0.1 μm to 100 μm, and therefore has a large surface area per unit volume, and can have a high removal rate of pollutants. In addition, if the particle size of the adsorbent particles is small, the voids are filled and the packing density becomes high, which results in high pressure loss. In this respect, in the adsorption filter according to the embodiment of the present invention, 500 or more pieces of the adsorbent B, which has a small average particle major axis, are fixed to the surface of the adsorbent A, which has a large average particle major axis of 200 μm to 1000 μm. As a result, voids are easily formed between the adsorbent particles in the adsorption filter, so that the packing density does not become too high. Furthermore, since 65% or more of the adsorbent B out of the total number (100%) of the adsorbent B is fixed to the surface of the adsorbent A, there is little adsorbent B present free from the surface of the adsorbent A, and it is possible to prevent the adsorbent B from filling the gaps in the substrate and causing clogging. As a result, an adsorption filter with low pressure loss can be obtained. When the adsorption filter according to the embodiment of the present invention is attached to and used in an air purification device such as an air purifier or air conditioner, the pressure difference between the upstream and downstream sides of the adsorption filter is small, improving the adsorption performance and contributing to energy saving.
[0015] When manufacturing an adsorption filter, adsorbent A with an average particle length of 200 μm to 1000 μm and adsorbent B with an average particle length of 0.1 μm to 100 μm can be obtained by sieving the adsorbent particles through a mesh. The mesh size can be selected according to the desired particle length, for example, adsorbent A with a large average particle length is obtained by removing particles that can pass through a mesh number 18 but cannot pass through a mesh number 65 or larger, and adsorbent B with a small average particle length is obtained by sieving through a mesh number 160 or larger.
[0016] After being manufactured as an adsorption filter, the major axis of the adsorbent A and the adsorbent B contained in the adsorption filter can be measured from a photograph obtained by removing at least a part of the substrate so that the adsorbent A and the adsorbent B can be observed, and then observing them with a microscope such as a scanning electron microscope (SEM). The major axis of the adsorbent A and the adsorbent B can be determined, for example, by observing 100 pieces of each of the adsorbent A and the adsorbent B with an SEM, measuring the length of the longest line segment among the lines connecting the outer edges of one particle, and taking the average of the measured values of the 100 pieces obtained. In the micrograph, if the shape of the particle is circular, the length of the line segment is the diameter of the outer edge, if the shape of the particle is elliptical, the length of the line segment is the major axis of the ellipse, and if the shape of the particle is rectangular, the length of the line segment is the length of the diagonal of the rectangle, but the shape of the particle is not limited to the above shapes. Whatever the shape of the particle, the major axis can be uniquely determined by the above definition.
[0017] The average particle major axis of the adsorbent A is 200 μm or more, preferably 250 μm or more, more preferably 300 μm or more, even more preferably 350 μm or more, particularly preferably 375 μm or more, and may be 400 μm or more. If the lower limit of the average particle major axis of the adsorbent A is within the above range, the pressure loss of the adsorption filter can be reduced. In addition, the average particle major axis of the adsorbent A is 1000 μm or less, preferably 900 μm or less, more preferably 850 μm or less, even more preferably 800 μm or less, and may be 750 μm or less. If the upper limit of the average particle major axis of the adsorbent A is within the above range, there is an advantage that the thickness of the adsorption filter does not become too thick and manufacturing is easy.
[0018] The average particle major axis of the adsorbent B is 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more. If the lower limit of the average particle major axis of the adsorbent B is within the above range, the cohesive force of the adsorbent B is not too strong, and the adsorbent B can be uniformly fixed to the surface of the adsorbent A. In addition, the average particle major axis of the adsorbent B is 100 μm or less, preferably 75 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. If the upper limit of the average particle major axis of the adsorbent B is within the above range, the adsorption force of the adsorbent B to the surface of the adsorbent A can be secured, and it is easy to prevent the adsorbent B from falling off from the adsorbent A. By having the average particle major axis of the adsorbent B within the above range, it is possible to uniformly and strongly adhere the adsorbent B to the surface of the adsorbent A.
[0019] The number of adsorbents B adhering to each particle of adsorbent A is 500 or more, preferably 600 or more, more preferably 800 or more, even more preferably 1,000 or more, and particularly preferably 2,000 or more. If the lower limit of the number of adsorbents B adhering to each particle of adsorbent A is within the above range, the surface area for adsorbing contaminants by adsorbent B can be increased, so that the removal rate of contaminants can be increased. The upper limit of the number of adsorbents B adhering to each particle of adsorbent A is not particularly limited, but may be, for example, 2,000,000 or less, more preferably 1,000,000 or less, more preferably 500,000 or less, particularly preferably 100,000 or less, 80,000 or less, 50,000 or less, 30,000 or less, 10,000 or less, 9,000 or less, or 8,000 or less. The number of particles of adsorbent B that can adhere to the surface of adsorbent A depends on the size of adsorbent B relative to the surface area of adsorbent A. However, if the upper limit of the amount of adsorbent B adhered to each particle of adsorbent A is within the above-mentioned range, adsorbent B is less likely to fall off the surface of adsorbent A, and clogging due to fallen adsorbent can be prevented, thereby reducing the pressure loss of the adsorption filter.
[0020] The number of adsorbents B adhering to each particle of adsorbent A can be obtained from a micrograph taken with a scanning electron microscope (SEM) or the like. The number of adsorbents B adhering to each particle of adsorbent A can be obtained, for example, by removing at least a portion of the substrate so that adsorbents A and B can be observed, observing 10 adsorbent particles with an SEM, counting the number of adsorbents B adhering to the surface of adsorbent A in each case, and then multiplying this number by two assuming that the same number of adsorbents B are adhering to the surface opposite to the observation surface, and averaging the measured values obtained for the 10 particles.
[0021] In the adsorption filter, when the total number of adsorbents B is 100%, the number of adsorbents B adhering to the surface of adsorbent A is 65% or more. Adsorbents B not adhering to the surface of adsorbent A may fill the voids of the substrate and increase the pressure loss of the adsorption filter, but since the number of adsorbents B adhering to the surface of adsorbent A is 65% or more out of the total number of adsorbents B (100%), the number of adsorbents B that are not adhering to the surface of adsorbent A and are free to fill the voids of the substrate is reduced, so that the pressure loss of the adsorption filter can be kept low. The proportion of adsorbents B adhering to the surface of adsorbent A is more preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, and particularly preferably 90% or more. If the lower limit of the proportion of adsorbents B adhering to the surface of adsorbent A is within the above range, the pressure loss of the adsorption filter can be reduced. The ratio of adsorbent B adhering to the surface of adsorbent A is ideally 100%, but may realistically be 99% or less, 98% or less, 96% or less, or 95% or less.
[0022] The proportion of adsorbent B adhering to the surface of adsorbent A can be obtained from a micrograph taken with a scanning electron microscope (SEM) or the like. The proportion of adsorbent B adhering to the surface of adsorbent A can be determined, for example, by removing at least a part of the substrate so that adsorbent A and adsorbent B can be observed, observing with an SEM so that at least 10 adsorbents A are included in one field of view, and counting the number of adsorbents B adhering to the surface of adsorbent A and the number of adsorbents B not adhering to the surface of adsorbent A but present in the gaps of adsorbent A in the field of view. The measurement may be performed by actually counting the number of adsorbents B, or by visually determining the number of adsorbents B adhering to the surface of adsorbent A and the number of adsorbents B not adhering to the surface of adsorbent A but present in the gaps of adsorbent A.
[0023] Average particle length R of adsorbent A A and the average particle length R of the adsorbent B B Ratio of R B / R A The ratio R is preferably 1 / 5000 to 1 / 5, more preferably 1 / 1000 to 1 / 10, further preferably 1 / 500 to 1 / 20, and most preferably 1 / 100 to 1 / 30. B / R A By setting the ratio R to 1 / 5000 or more, the cohesive force of adsorbent B is not too strong, and adsorbent B can be uniformly fixed to the surface of adsorbent A. B / R A By making the size of adsorbent B relative to the surface area of adsorbent A be 1 / 5 or less, the size of adsorbent B relative to the surface area of adsorbent A does not become too large, making it easier to ensure the adhesive force of adsorbent B to the surface of adsorbent A and preventing adsorbent B from falling off from adsorbent A.
[0024] Average particle length R of adsorbent A A , the average particle major axis R of the adsorbent B B and the weight ratio P of the adsorbent A to the adsorbent B ((weight of adsorbent A) / (weight of adsorbent B)) preferably satisfies the relationship of the following formula (1). P=R A 3 / [{(R A +2R B ) 3 -R A3}×X] ···(1)
[0025] Equation (1) indicates that the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) corresponds to (volume of adsorbent A) / (volume of adsorbent B). Here, the volume of adsorbent A is approximately R A 3 In addition, it is assumed that adsorbent B is fixed to both sides of adsorbent A, and the major axis R of adsorbent A is A The major axis R of adsorbent B is B The volume of adsorbent A with adsorbent B adhering to its surface is calculated by cubed (R A +2R B ) 3 From this, the volume of adsorbent A, R A 3 By subtracting A +2R B ) 3 -R A 3 The smaller X is, the smaller the amount of adsorbent B adhering to the surface of adsorbent A is, and the larger X is, the larger the amount of adsorbent B adhering to the surface of adsorbent A is.
[0026] X is preferably 0.1 to 10, more preferably 0.2 to 8.0, even more preferably 0.4 to 5.0, and most preferably 0.5 to 2.0. If X is within this range, it is easy to uniformly fix the adsorbent B to the surface of the adsorbent A. If X is less than 0.1, the amount of the adsorbent B is too small, making it difficult to obtain the effects of the present invention. If X is greater than 10, it is considered that multiple layers of the adsorbent B are deposited on the surface of the adsorbent A, and even if the amount of the adsorbent B is increased so that X is greater than 10, it is unlikely that the effect of reducing the pressure loss of the adsorption filter will be improved compared to when X is 0.1 to 10. Conversely, if X is too large, it is considered that the adsorbent B is easily detached from the surface of the adsorbent A, thereby increasing the pressure loss of the adsorption filter. From this viewpoint, X is preferably 15 or less, more preferably 12 or less.
[0027] Adsorbent A and adsorbent B are preferably made of a material capable of capturing ions or molecules of contaminants, such as toluene or acetaldehyde, contained in the gas phase, thereby removing them from the gas phase.
[0028] The adsorbent A is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent A is preferably composed of activated carbon or silica gel.
[0029] The adsorbent B is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent B is preferably composed of activated carbon or silica gel.
[0030] The material constituting adsorbent A and the material constituting adsorbent B may be the same or different, but are preferably the same, which can ensure the adhesive force of adsorbent B to the surface of adsorbent A.
[0031] The activated carbon is not particularly limited, but it is preferable to use common activated carbon such as coconut shell activated carbon, coal-based activated carbon, wood-based activated carbon, and synthetic resin-based activated carbon in terms of performance and availability.
[0032] The BET specific surface area of the activated carbon is not particularly limited, but is preferably 800 m 2 / g~1500m 2 / g is preferred, and 850m 2 / g~1300m 2 / g is more preferable. 2 / g or more, it is easy to obtain a deodorizing effect. In addition, the BET specific surface area of the activated carbon is 1500 m2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0033] The pore volume of the activated carbon is not particularly limited, but is preferably 0.30 cm 3 / g~0.70cm 3 / g is preferred, and 0.40 cm 3 / g~0.55cm 3 / g is more preferable. 3 / g or more, the deodorizing effect is easily obtained. 3 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0034] The average pore diameter of the activated carbon can be appropriately adjusted depending on the object to be adsorbed. For example, when the object to be adsorbed is toluene, the average pore diameter is preferably 15 Å to 19 Å, and more preferably 16 Å to 18 Å.
[0035] The BET specific surface area of the silica gel is not particularly limited, but is preferably 20 m 2 / g~1000m 2 / g is preferred, 50m 2 / g~700m 2 / g is more preferable. The BET specific surface area of the silica gel is 20 m 2 / g or more, the deodorizing effect is easily obtained. In addition, the BET specific surface area of the silica gel is 1000 m 2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0036] It is preferable that the adsorbent B is fixed to the surface of the adsorbent A via a binder. This makes it easy for the adsorbent B to be fixed to the surface of the adsorbent A, and makes it easy to prevent the adsorbent B from falling off the surface of the adsorbent A. As a result, it is possible to prevent the adsorbent B that has fallen off the surface of the adsorbent A from filling up the voids in the adsorption filter, thereby preventing an increase in pressure loss.
[0037] The binder is not particularly limited as long as it can fix the adsorbent B to the surface of the adsorbent A, and examples thereof include water-soluble polymers, thermoplastic resins, and water-dispersible polymers. In particular, the binder is preferably a water-soluble polymer. The water-soluble polymer preferably has a solubility in water of 1 g or more at 20° C. and 1 atm, and a molecular weight of 10,000 or more. The binder is preferably a water-soluble polymer, and is preferably at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
[0038] By using a water-soluble polymer as the binder, adsorbent B can be easily fixed to the surface of adsorbent A even if only a small amount of binder is added.
[0039] The binder solution concentration is preferably 0.1% by weight to 10% by weight, and more preferably 1% by weight to 5% by weight. By setting the binder solution concentration to 0.1% by weight or more, the adhesive force of adsorbent B to the surface of adsorbent A can be ensured. By setting the binder solution concentration to 10% by weight or less, the problem of the binder coating the adsorbent particles, which occurs when the binder solution concentration exceeds 10% by weight, can be avoided. The binder solution concentration may be the solution concentration of the water-soluble polymer.
[0040] The method for fixing adsorbent B to the surface of adsorbent A is not particularly limited, but examples thereof include a method in which adsorbent A and adsorbent B are immersed in an aqueous solution in which a water-soluble polymer is dissolved, stirred, and then dried, and a method in which an aqueous solution in which a water-soluble polymer is dissolved is made into a mist or mist form and sprayed onto adsorbent A and adsorbent B, and then dried.
[0041] The adsorption filter can be obtained by supporting the above-mentioned adsorbent A and adsorbent B on a substrate. The substrate is preferably molded into a planar, pleated, or honeycomb shape. When used as a cross-flow filter, the pleated shape increases the contact area with the gas to be treated, improving the removal rate of pollutants, while simultaneously realizing low pressure loss in the filter.
[0042] The method of supporting the adsorbent A and the adsorbent B on the substrate is not particularly limited, and a known processing method can be used. For example, (a) a wet sheeting method in which the adsorbent A and the adsorbent B are dispersed in water together with the fibers constituting the substrate and dehydrated, (b) an airlaid method in which the adsorbent A and the adsorbent B are dispersed in air together with the fibers constituting the substrate, (c) a method in which the adsorbent A and the adsorbent B are filled between two or more layers of nonwoven fabric, woven fabric, net-like material, film, membrane, etc. by thermal adhesion, (d) a method in which the adsorbent A and the adsorbent B are bonded and supported on a breathable material such as a nonwoven fabric, a woven fabric, or a urethane foam using an emulsion adhesive or a solvent-based adhesive, (e) a method in which the adsorbent A and the adsorbent B are bonded and supported on a breathable material such as a nonwoven fabric, a woven fabric, or a urethane foam using the thermoplasticity of a thermoplastic resin, and (f) a method in which the adsorbent A and the adsorbent B are mixed and integrated by kneading them into a fiber or a resin, etc., can be used according to the application. In particular, among the above processing methods, it is preferable to use processing methods (b), (c), and (e) since it is not necessary to use a surfactant and it is possible to prevent the adsorbent from being covered with the surfactant.
[0043] When the above-mentioned adsorbent A and adsorbent B are supported on a substrate, it is preferable to support the adsorbent A having the adsorbent B fixed on its surface on the substrate. That is, in the above-mentioned methods (a) to (f), "adsorbent A and adsorbent B" can be read as "adsorbent A having the adsorbent B fixed on its surface." This makes it possible to easily fix the adsorbent B to the surface of the adsorbent A.
[0044] The substrate is preferably a nonwoven fabric. The type of nonwoven fabric is not particularly limited, but is preferably a needle-punched nonwoven fabric that can be formed by piercing needles with protrusions to entangle fibers, a spunlace nonwoven fabric that can be formed by entangling fibers with a high-pressure water flow, a spunbond nonwoven fabric that can be formed by bonding a web formed from long fibers into a sheet, or a laminate thereof. When stacking nonwoven fabrics, it is preferable to bond each layer using, for example, a needle. The substrate may be an electret nonwoven fabric obtained by electrically charging a nonwoven fabric. Needless to say, the substrate may be a material other than a nonwoven fabric, and the substrate of the nonwoven fabric may contain another material such as a knitted fabric or a woven fabric.
[0045] The adsorption filter can remove ions and molecules contained in the gas phase, such as toluene and acetaldehyde, from the target gas phase by capturing them therein, and can be used for various purposes. Although not particularly limited, the adsorption filter can be used indoors, in vehicles, etc., and is preferably used in wallpaper, furniture, interior materials, resin molded bodies, electrical equipment, etc. EXAMPLES
[0046] The present invention will be described below with reference to examples. The present invention is not limited to the examples, and any design modifications made in accordance with the spirit described above and below are included within the technical scope of the present invention.
[0047] (Number of adsorbents B adhering to adsorbent A) Ten pieces of each of the adsorbents obtained in each of the Examples and Comparative Examples were observed under a scanning electron microscope (SEM). From the SEM observation photographs, the number of pieces of adsorbent B adhering to the surface of each piece of adsorbent A was counted. Assuming that the same number of pieces of adsorbent B were adhering to the side opposite to the observation side, this number was doubled, and the average of the obtained 10 measurements was taken as the number of pieces of adsorbent B adhering to adsorbent A. In this case, the tens digit was rounded off.
[0048] (Proportion of adsorbent B adhering to adsorbent A) One side of the nonwoven fabric was peeled off from the adsorption filter obtained in each Example and Comparative Example, and the filter was observed with a scanning electron microscope (SEM) so that at least 10 particles of adsorbent A were included in one field of view. Of the total number of adsorbents B captured in the SEM observation photograph (100%), the number of particles of adsorbent B adhering to the surface of adsorbent A and the number of particles of adsorbent B not adhering to the surface of adsorbent A but existing in the gaps between adsorbent A were determined by visual estimation, and the proportion of adsorbent B adhering to adsorbent A was calculated.
[0049] (Toluene removal rate) Cross-sectional area 36cm 2 A sheet-formed adsorbent (adsorption filter) was sandwiched between the columns. Air with a toluene vapor concentration of 80 ppm was supplied to the column at a linear velocity of 20 cm / sec, a temperature of 25°C, and a humidity of 50% RH. The toluene concentration at the column outlet was measured after 1 minute, and the removal rate (η) was calculated using the following formula (2). In the following formula (2), Ci (ppm) is the toluene inlet concentration, and Co (ppm) is the toluene outlet concentration. The toluene concentration was measured using a hydrocarbon system. Removal rate η(%)=[1-(Co / Ci)]×100 ···(2)
[0050] (Pressure loss) A sheet of adsorbent (adsorption filter) was placed inside the duct, and the linear velocity passing through the filter was controlled to be 10.4 cm / sec. The pressure loss (mmaq) was calculated by reading the static pressure difference upstream and downstream of the filter with a pressure gauge.
[0051] <Example 1> Adsorbent A was granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3Activated carbon powder and granular activated carbon (17Å / g, average pore size) were mixed in a weight ratio of 3:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon, and then mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent with powdered activated carbon fixed to the surface of the granular activated carbon.
[0052] The downstream layer is a thermal bond nonwoven fabric, and the above-obtained absorbent is mixed with a thermoplastic powder resin as an adhesive in a weight ratio of 20:1 to form a 200g / m2 2 The adsorption filter was heated using an electret nonwoven fabric as the upstream layer, and an adsorption filter in which the adsorbent was supported on the nonwoven fabric was obtained. For this adsorption filter, the number of adsorbent B adhering to adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 1.
[0053] <Comparative Example 1> Granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 The adsorption filter was fabricated by forming a sheet of a thermobond nonwoven fabric as the downstream layer, and the above adsorbent and a thermoplastic powder resin as an adhesive were mixed in a weight ratio of 20:1 to form a sheet with a basis weight of 200 g / m2. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 1.
[0054] [Table 1]
[0055] In Example 1 and Comparative Example 1, the pressure loss was equivalent because the average particle length of the granular activated carbon (adsorbent A) used was the same. However, since powdered activated carbon (adsorbent B) was not used in Comparative Example 1, the toluene removal rate was lower than that of Example 1.
[0056] <Example 2> Adsorbent A was granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 Activated carbon powder and granular activated carbon (17Å / g, average pore size) were mixed in a weight ratio of 7:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon, and then mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the granular activated carbon. An SEM image of the obtained adsorbent is shown in Figure 1.
[0057] The downstream layer is a thermal bond nonwoven fabric, and the above-mentioned absorbent and thermoplastic powder resin as an adhesive are mixed in a weight ratio of 20:1 to form a 200g / m2 2 The adsorption filter was heated using an electret nonwoven fabric as the upstream layer, and an adsorption filter in which the adsorbent was supported on the nonwoven fabric was obtained. For this adsorption filter, the number of adsorbent B adhering to adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 2. Also, an SEM photograph taken after peeling off the nonwoven fabric on one side is shown in Figure 2.
[0058] <Example 3> An adsorption filter was manufactured in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 50:1. The manufacturing conditions and measurement results are shown in Table 2.
[0059] <Example 4> An adsorption filter was manufactured in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 1:1. The manufacturing conditions and measurement results are shown in Table 2.
[0060] <Example 5> An adsorption filter was manufactured in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 1:2. The manufacturing conditions and measurement results are shown in Table 2.
[0061] <Example 6> Except for changing the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon to 9.0% by weight, an adsorptive filter was manufactured in the same manner as in Example 2. The manufacturing conditions and measurement results are shown in Table 2.
[0062] <Example 7> Except for changing the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon to 2.0% by weight, an adsorptive filter was manufactured in the same manner as in Example 2. The manufacturing conditions and measurement results are shown in Table 2.
[0063] <Example 8> An adsorption filter was manufactured in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 80000. The manufacturing conditions and measurement results are shown in Table 2.
[0064] <Example 9> An adsorption filter was manufactured in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 100,000. The manufacturing conditions and measurement results are shown in Table 2.
[0065] <Example 10> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinyl alcohol (PVA) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the polyvinyl alcohol (PVA) was 90,000. The manufacturing conditions and measurement results are shown in Table 2.
[0066] <Example 11> An adsorptive filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4 wt% aqueous polyacrylamide (PAM) solution instead of the aqueous sodium alginate (ALG-Na) solution. The manufacturing conditions and measurement results are shown in Table 2.
[0067] <Example 12> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of carboxymethylcellulose (CMC) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the carboxymethylcellulose (CMC) was 120,000. The manufacturing conditions and measurement results are shown in Table 2.
[0068] <Example 13> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinylpyrrolidone (PVP) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of polyvinylpyrrolidone (PVP) was 360,000. The manufacturing conditions and measurement results are shown in Table 2.
[0069] <Example 14> Adsorbent A was granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was manufactured in the same manner as in Example 2, except that adsorbent A and adsorbent B were mixed in a weight ratio of 10:1 using 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether, ...) (0.1% / g, average pore size 17 Å) and adsorbent A and adsorbent B were mixed in a weight ratio of 10:1. The manufacturing conditions and measurement results are shown in Table 2.
[0070] <Example 15> Adsorbent B was powdered activated carbon (average particle length 50 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was manufactured in the same manner as in Example 2, except that adsorbent A and adsorbent B were mixed in a weight ratio of 2:1 using 1000 g / g (average pore size 17 Å). The manufacturing conditions and measurement results are shown in Table 2.
[0071] <Example 16> Adsorbent B was powdered activated carbon (average particle length 1 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was manufactured in the same manner as in Example 2, except that adsorbent A and adsorbent B were mixed in a weight ratio of 100:1 using 1,2-dichlorophenyl ether (1,2-dichlorophenyl ether, ...) (0.1% / g, average pore size 17 Å) and adsorbent A and adsorbent B were mixed in a weight ratio of 100:1. The
[0072] [Table 2]
[0073] <Comparative Example 2> The downstream layer is made of thermal bond nonwoven fabric, and the downstream layer is made of granular activated carbon (average particle length 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 20:1, and the resulting mixture had a basis weight of 200g / m 2 The mixture was sprayed so that the concentration of the activated carbon in the adsorption filter was 100%. An electret nonwoven fabric was used as the upstream layer and heated to obtain an adsorption filter in which granular activated carbon was supported on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3.
[0074] <Comparative Example 3> Granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was produced in the same manner as in Comparative Example 2, except that 1,2-dichloromethane (1.0 μm / g, average pore size 17 Å) was used. The production conditions and measurement results are shown in Table 3.
[0075] <Comparative Example 4> The downstream layer was a thermal bond nonwoven fabric, and the adsorbent A was granular activated carbon (average particle length 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 7:1:0.4 to give a basis weight of 200g / m 2 The adsorption filter was heated using an electret nonwoven fabric as the upstream layer, and an adsorption filter in which the adsorbent was supported on the nonwoven fabric was obtained. For this adsorption filter, the number of adsorbent B adhering to the surface of adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3. Also, an SEM photograph taken after peeling off the nonwoven fabric on one side is shown in FIG. 3.
[0076] <Comparative Example 5> An adsorption filter was manufactured in the same manner as in Example 2, except that the weight ratio of adsorbent A to adsorbent B was changed to 200:1. The manufacturing conditions and measurement results are shown in Table 3.
[0077] <Comparative Example 6> The downstream layer is made of thermal bond nonwoven fabric, and the downstream layer is made of granular activated carbon (average particle length 150 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 20:1, and the resulting mixture had a basis weight of 200g / m 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3.
[0078] [Table 3]
[0079] As can be seen from Table 2, the adsorption filters of Examples 2 to 16 had a high toluene removal rate and reduced pressure loss.
[0080] In contrast, as can be seen from Table 3, in Comparative Examples 2 and 3 in which adsorbent B was not used, the toluene removal rate was low. In Comparative Example 4 in which adsorbent A and adsorbent B were mixed at a weight ratio of 7:1 but the proportion of adsorbent B adhering to the surface of adsorbent A was small, the toluene removal rate was high, but the pressure loss of the adsorption filter was high. This is thought to be because the proportion of adsorbent B that was not attached to adsorbent A and was free was high, so that adsorbent B filled the gaps between the fibers of the nonwoven fabric and caused clogging. In Comparative Example 5 in which adsorbent B was used but the weight ratio of adsorbent A to adsorbent B was 200:1, the toluene removal rate was low because the number of adsorbent B was small. In Comparative Example 6 in which activated carbon with an average particle major axis of 150 μm, which does not correspond to adsorbent A or adsorbent B, was used alone, the toluene removal rate was high, but the pressure loss of the adsorption filter was high.
[0081] Fig. 4 shows a graph illustrating the relationship between the toluene removal rate and pressure loss for the adsorption filters of Examples 1 to 16 and Comparative Examples 1 to 6. The horizontal axis is pressure loss (mmaq) and the vertical axis is toluene removal rate (%). Fig. 4 shows that the adsorption filters of Examples 1 to 16 have a high toluene removal rate relative to the pressure loss, while the adsorption filters of Comparative Examples 1 to 6 have a low toluene removal rate relative to the pressure loss.
[0082] As described above, the adsorption filter of the present invention has a high toluene removal rate and is capable of reducing pressure loss.
[0083] <Example 17> Adsorbent A was silica gel (average particle length 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 24 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) were mixed in a weight ratio of 7:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the silica gel and powdered activated carbon and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the silica gel. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0084] <Comparative Example 7> Instead of granular activated carbon, silica gel (average particle diameter 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 Except for using an adsorbent of 1000 g / g and an average pore size of 24 Å, an adsorption filter was obtained in the same manner as in Comparative Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0085] [Table 4]
[0086] FIG. 5 is a graph showing the relationship between the toluene removal rate and pressure loss when the adsorption filter is made using the adsorbent of Example 17, which uses silica gel as the adsorbent A, and the adsorbent of Comparative Example 7. The horizontal axis is pressure loss (mmaq), and the vertical axis is toluene removal rate (%). From Table 4 and FIG. 5, it can be seen that the filter using the adsorbent of Example 17 has a high toluene removal rate relative to the pressure loss, and the filter using the adsorbent of Comparative Example 7 has a low toluene removal rate relative to the pressure loss. From this, it can be seen that the effect of the present invention can be achieved by adsorbent B being fixed to the surface of adsorbent A, regardless of the type of adsorbent. [Industrial Applicability]
[0087] By using the adsorption filter of the present invention, it is possible to remove contaminants including volatile organic compounds such as toluene and aldehydes efficiently with low pressure loss, which is expected to make a great contribution to the industrial world.
Claims
1. The present invention includes an adsorbent A having an average particle length of 200 μm to 1000 μm, an adsorbent B having an average particle length of 0.1 μm to 100 μm, and a substrate, The adsorbent A and the adsorbent B are supported on the substrate, 500 or more particles of the adsorbent B are fixed to each particle of the adsorbent A, An adsorption filter in which 65% or more of the adsorbent B is adhered to the surface of the adsorbent A, when the total amount of the adsorbent B is taken as 100%.
2. The average particle length R of the adsorbent A A and the average particle major axis R of the adsorbent B B Ratio of R B / R A The adsorption filter according to claim 1, wherein the ratio of the adsorption amount to the total adsorption amount is 1 / 5000 to 1 / 5.
3. The average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B and the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) of the adsorbent A and the adsorbent B is P=R A 3 / [{(R A +2R B ) 3 -R A 3 3. The adsorption filter according to claim 1, wherein the relationship: x x is 0.1 or more and 10 or less.
4. 3. The adsorption filter according to claim 1, wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite.
5. 3. The adsorption filter according to claim 1, wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite.
6. 3. The adsorption filter according to claim 1, wherein the adsorbent B is fixed to the surface of the adsorbent A via a binder.
7. The adsorption filter according to claim 6, wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
8. 3. The adsorption filter according to claim 1, wherein the substrate is a nonwoven fabric.
Citation Information
Patent Citations
Filter medium
JP2015157250A
Cohesive activated carbon air filter
JP3612329B2